The coexistence of maternal overweight or obesity and child stunting in low-income country: Further data analysis of the 2016 Ethiopia demographic health survey (EDHS) - Tewodros Eshete; Gemechu Kumera; Yibelu Bazezew; Tefera Marie; Simegn Alemu; Kirubel Shiferaw (Scientific African, 2020)
Background: Malnutrition is one of the global public health problem that exists in many forms. The dual burden household, particularly the stunted child/overweight or obese mothers is a commonly described phenomenon in low and middle income countries. This study aims to assess the level and determinants of coexistence of stunted child and overweight/obese mothers in Ethiopia Methods: This study utilized the Ethiopian Demographic health survey of 2016 to explore significant predictors that plays significant role among overweight or obese mothers to have stunted child. Using the WHO guidelines, we considered mothers with a body mass index of >25 kgm−2 as overweight/obese and height for age z-scores were used for assessing nutritional status of children. Statistical analysis was conducted using multiple logistic regression with p<0.05 for declaration of statistical significant association between independent and dependent variables. Results: Around 23% of mothers who were overweight or obese in Ethiopia had stunted child. The odds of coexistence among mothers who attained primary school education were 44% less likely than mothers who had no formal education with AOR 0.56, 95% CI [0.28, 1.09]. The odds of double burden of malnutrition among mothers living in rural residence was 2.06 times higher than women who were in urban areas AOR 2.06, 95% CI [1.08, 3.93]. The other factor which shows statistically significance was age of the child at the time of interview with AOR 4.94, 95% CI [1.75, 14.04]. Conclusion: The double burden of over and undernutrition in a household is a burden in Ethiopia that has to be integrated in nutrition strategies. Nutritional education has to be provided for overweight/obese mothers with stunted children in reducing the double burden of malnutrition.